Institutional Analysis for Multimodal Transport to Support Logistic System in Port of Tanjung Priok: Methodological Framework - Nurullah - Budisiswanto; Miming Miharja; P. Pradono; B. Kombaitan (International Journal of Supply Chain Management, 2017)
Abstract- In Indonesia, The absence of an institution that has the authority to coordinate and strengthen national commitment to the implementation of logistics policy is a constraint in the institutional system of national logistics in Indonesia. This paper conducted a review of the methodology of institutional framework to support cheap, fast and safe multimodal transport logistics system in port of tanjung priok, in an effort to objectify the institutional coordination concept of multimodal transport that can properly support the attainment of the vision in the development of the national logistics system. The method used in the form of qualitative descriptive to explore aspects of transport such as patterns of institutional coordination, range of powers and the institutional level. Meanwhile, multi-methods is used to select the proper transport institutional patterns according to the stakeholders associated with multimodal logistics activities in Indonesia.